Whole blood transcriptome profile at hospital admission discriminates between patients with ST-segment elevation and non-ST-segment elevation acute myocardial infarction - Chiesa, Mattia (Sci Rep, 2020)
Whether ST-segment (STEMI) and non-ST-segment elevation myocardial infarction (NSTEMI) should be regarded as distinct pathophysiological entities is a matter of debate. We tested the hypothesis that peripheral blood gene-expression profiles at presentation distinguish STEMI from NSTEMI. We performed a case-control study collecting whole-blood from 60 STEMI and 58 NSTEMI (defined according to the third universal definition of MI) consecutive patients on hospital admission. We used RNA-sequencing for the discovery phase, comparing 15 STEMI vs. 15 NSTEMI patients, matched for age, sex, and cardiovascular risk factors, and quantitative PCR in the remaining unmatched patients for validating top-significant genes. Gene-level differential expression analysis identified significant differences in the expression of 323 genes: 153 genes withstood correction for admission cardiac troponin I (cTnI), differentiating the two conditions independently of myocardial necrosis extent. Functional annotation analysis uncovered divergent modulation in leukocyte and platelet activation, cell migration, and mitochondrial respiratory processes. Linear regression analysis revealed gene expression patterns on admission predicting infarct size, as indexed by cTnI peak (R(2) = 0.58–0.75). Our results unveil distinctive pathological traits for these two MI subtypes and provide insights into the early assessment of injury extent. This could translate into RNA-based disease-specific biomarkers for precision diagnosis and risk stratification.